Research into Public Debt Indicators and Debt Effects on Lithuania’s Economy - Barkauskaitė, Aida; Šimkus, Antanas (Jaunųjų mokslininkų darbai, 2015)
Government borrowing is inevitable when a country faces a lack of financial resources. The characteristics of public debt, its advantage and impact on a country’s economy have been analyzed by such researchers as Buškevičiūtė, (2008), Martin (2009), Karazijienė & Sabonienė (2009), Rosen & Gayer (2010), Kumar & Woo (2010) but scientific literature on changes in public debt indicators and their impact on Lithuania’s economy have been lacking. The rising costs of servicing public debt inevitably means that a country will have to collect bigger revenues and impose higher taxes for both, individuals and entities. The aim of this research is to identify trends in public debt and the impact of debt indicators on Lithuania’s economy. Research methodology: scientific literature overview, comparative analysis, graphical data analysis. The research showed that although economic indicators for Lithuania improved during 2010-2013, its public debt continued to rise. During 2006-2012 interest rate also showed a growth tendency. The situation changed in 2013 when interest rate reduced by 6.1%. Most of public debt indicators such as interest rate, the debt-to-GDP ratio, budget expenditure, etc. improved during the analyzed period, the debt-to-GDP ratio, for example, increased more than two times. It should be noted that in 2013 public debt indicators showed a downward tendency compared to the previous year and public debt slightly decreased. Analysis shows that government can make a significant impact on a country’s economy, a strong positive correlation was identified between public debt and GDP, the unemployment rate and deposited amounts but no statistically significant linear correlation was identified between public debt and the inflation rate. A country’s government should understand the significance of public debt and carefully assess its impact on a country’s economy and population when taking a decision to borrow.